Analisis Etika Diskursus Jurgen Habermas terhadap Demokrasi Cair pada Masyarakat Digital - Febriani, Rika; Supartiningsih, Supartiningsih; Tjahyadi, Sindung; Hertanti, Rachmi (Universitas Negeri Malang, 2024)
The purpose of writing this article is to describe the basic concept of liquid democracy and analyze the principles of liquid democracy in digital society based on Jurgen Habermas’ discourse ethics. This study uses a historical-factual method based on the view that humans are historical creatures that develop in thought and experience. Liquid democracy is a system that allows each individual to convey aspirations directly or delegate aspirations to others who are more expert in the decision-making process. The application of liquid democracy in digital society is based on the principles of Jurgen Habermas’ discourse ethics which are divided into two types, namely universal and discourse principles. Universal principles relate to the interests and needs of each individual in the decision-making process. Discourse principles relate to procedures in the decision-making process based on certain norms.